Current Status Of Ophthalmic In-Situ Forming Hydrogel - KATARIYA DHIRAJKUMAR CHAMPALAL,; PODDAR SUSHILKUMAR S., (International Journal of Pharma and Bio Sciences, 2012)
Ophthalmic drug delivery is one of the most interesting and challenging endeavors faced by the pharmaceutical scientist. The conventional ocular drug delivery systems like solutions, suspensions and ointments show drawbacks such as increased precorneal elimination, high variability and blurred vision. Low absorption results in short duration of action and high frequency of eye drop instillation are associated with discomfort to the patient. Delivery of a therapeutic agent can be improved by developing novel systems for example through penetration enhancers or by altering its physicochemical properties. In the novel delivery system various approaches are used like In-situ gelling, use of mucoadhesive polymers, polymer coated Nanoparticle and Liposomal formulation. The primary focus of the review is to give an insight in to the novel drug delivery to delay elimination from eye and to improve corneal penetration of drug molecule.